Improvement of dye sensitized solar cells efficiency utilizing diethyl carbonate in PVA based gel polymer electrolytes - Aziz, M. F. (Indonesian Society for Knowledge and Human Development, 2022)
Low conductivity of gel polymer electrolytes (GPEs) containing double iodide salts is critical for efficiency in dye-sensitized solar cells (DSSCs). The presence of diethyl carbonate (DEC) plasticizer affects the amorphousness and ionic conductivity of polyvinyl alcohol (PVA)-based GPEs and DSSCs performance. In this work, PVA-based GPEs containing a variation of DEC have been produced, characterized, and applied in the DSSCs fabrication. The structural properties of GPEs were analyzed using X-ray diffraction (XRD). The ionic conductivity was determined from electrical impedance spectroscopy (EIS). Based on XRD, GPEs for all prepared compositions have been identified as an amorphous phase. From the EIS measurement, it was found that GPE with the composition of 5.46 PVA - 8.19 EC - 10.92 PC - 60.06 DMSO - 5.73 TPAI - 5.73 KI - 1.34 I2 - 2.57 DEC (in wt. %) having highest conductivity of 11.19 Â± 0.20 mS cm-1 with activation energy, Ea of 0.09 eV. The graph of conductivity versus temperature following the Arrhenius rule has been plotted. The GPEs dominate the highest conductive with 2.57% of DEC and showed the DSSCs efficiency of 6.42%. Common DSSCs parameters resulted in short-circuit current density (Jsc) of 17.58 mA cm-2, fill factor (ff) of 0.63, and open-circuit voltage (Voc) of 0.58 V. In conclusion, DEC improves the ionic conductivity as well as amorphous properties of the GPE, and therefore enhance the DSSCs’ efficiency.